Three-phonon relaxation in isotropic and anisotropic phonon systems of liquid helium at different pressures - Adamenko, I.N.; Kitsenko, Yu.A.; Nemchenko, K.E.; Slipko, V.A.; Wyatt, A.F.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Starting from the kinetic equation for phonons in superfluid helium, expressions for the rates of three-phonon scattering in isotropic and anisotropic phonon systems were obtained for different pressures. These expressions are valid in the whole range of energies where three-phonon processes are allowed. Limiting cases were analysed and compared with the results of previous theoretical investigations.The obtained pressure and angular dependence of three phonon scattering rate allows one to explaine of the experimental data on interaction of phonon pulses.